2017
DOI: 10.3184/175815617x14878495604643
|View full text |Cite
|
Sign up to set email alerts
|

Wintering Behaviour and Spatial Ecology of Eurasian Wigeon Anas Penelope in a Coastal Mediterranean Wetland Complex (Guerbes-Sanhadja) of Northeastern Algeria

Abstract: As rare and threatened species, ecological information about common waterbirds is needed to assess priorities for wetland management. In this study, we attempt to provide information about the spatial ecology and wintering behaviour of one of the most common species of the coastal Mediterranean wetland complex of northeastern Algeria, the Eurasian Wigeon Anas penelope. Over the three winters of the study the maximum number of recorded Eurasian Wigeon across all sites rose from 1,096 in 2010/11 to 1,397 in 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Good plumage maintenance provides good thermal insulation against the outside cold of winter and good insulation against water (Bezzalla et al 2019b). It also allows the Anatidae to be well prepared for the prenuptial migration (Bouchaala et al 2017).…”
Section: Behavioral Time Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…Good plumage maintenance provides good thermal insulation against the outside cold of winter and good insulation against water (Bezzalla et al 2019b). It also allows the Anatidae to be well prepared for the prenuptial migration (Bouchaala et al 2017).…”
Section: Behavioral Time Budgetmentioning
confidence: 99%
“…Wildfowl Anatidae are the main species of waterbirds that use North African wetlands, especially Algeria, for wintering and reproduction (Samraoui and Samraoui 2008;Sayoud et al 2017). Several studies have surveyed the behavior of Anatidae in Algerian wetlands (Boulkhssaim et al 2006;Samraoui 2001, 2008;Bouchaala et al 2017). However, beyond the description of time budgets of bird activities, nothing has been done to explain ecologically behavioral changes and habitat use nor the environmental factors influencing the observed activity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…, 2017,Bouchaala et al, 2017, Oudihat et al, 2017, Khemis et al, 2017a, 2017b, Charchar et al, 2019, Bezzala et al, 2019a, 2019b and in the lake(Figure 4). The Ferruginous Duck Aythya nyroca and the Whiteheaded Duck Oxyura leucocephala, Mallard Anas platyrhynchos, are regular sedentary nesting species in the Lac des Oiseaux.…”
mentioning
confidence: 93%
“…Waterbirds are considered to be indicators of the quality and the importance of wetlands regarding both biodiversity and ecosystem functions (Farinós Celdrán, Robledano, Perona, & Soto, ; Ma et al, ; Sadoul, ); in particular, changes in the structure and function of waterbird communities have been linked to changes in the biological integrity of wetlands (Farinós Celdrán et al, ; Pöysä et al, ). Ducks (genus Anas ) are one of the most common inhabitants of wetland ecosystems in temperate areas of the Northern Hemisphere (Bouchaala, Elafri, Charchar, Boukhemza, & Houhamdi, ). In the European wetlands, Eurasian wigeon (hereafter wigeon) Mareca penelope L. has a crucial role in food chain both as prey, for higher levels, and, as primary consumer, transferring energy up the food web (Jiménez‐Ramos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors already have studied the relationships between wigeon and seagrasses (Borum et al, ; Bouchaala et al, ; Nacken & Reise, ; Valentine & Heck Jr, ). For example, in Northern Sea, Vermaat and Verhagen () showed that the rapid decline in biomass from mid‐September onwards could be attributed to grazing by herbivorous migratory waterbirds and it was estimated that wigeon can remove 65 g ash‐free dry weight (AFDW) per bird per day.…”
Section: Introductionmentioning
confidence: 99%